Genesis and structural arrangement of the collapsed Oued Gueniche plain and the surrounding folds (Neogene molassic basin of Bizerte, northeastern Tunisia): Insights from gravity data - Zaghdoudi, Sabrine; Kadri, Ali; Ben Alayet, Mouna; Bounasri, Mohamed Aymen; Essid, El Mabrouk; Gasmi, Mohamed (Journal of African earth sciences (1994), 2021)
The Oued Gueniche plain is located in the northeastern Tunisia. It is a part of the Bizerte Neogene molassic basin, developed at the front of the Alpine chain (The Maghrebides). The subsurface structure of this area is not enough explored and was subject of controversial interpretations. Gravity and seismic data acquired in the northeast of Tunisia were used to specify the subsurface structural configuration and the formation mechanism of the Oued Gueniche plain, as well as, its relationship with the surrounding folds. A total number of 664 gravity measurements were used to define the density distributions below the surface in the study area. The complete Bouguer gravity anomaly was performed with a reduction density of 2.4 g/cm3. Bouguer anomalies range from 9.5 to 34.8 mGal, high anomalies coincide with the Oued Gueniche plain in the northwest while weak anomalies are located on the southern part of the study area. The main NE-SW anomalies are superposed to the geological structures. The power spectrum of gravity data shows that the calculated average depth to the top of regional gravity sources is approximately 4 km while that of local (or residual) sources is approximately 0.6 km. The techniques for locating the limits of anomalous structures and estimating their depths (tilt derivative (TDR), Euler deconvolution (ED) and analytical signal (AS)) were applied to the Bouguer anomaly map to further specify the underground geological characteristics. The maxima of the horizontal gradient magnitudes (MGH) of Bouguer anomalies, upward continuated at different altitudes, revealed several NE-SW and E-W trending lineaments. A three-dimensional (3D) inversion model of gravity data has been developed for the Oued Gueniche plain in order to follow the distribution of densities. In addition, the interpretation of seismic profiles indicates that the central part of this plain is marked by the diapirism of Triassic rocks. The combination of these results with those of the surface (geological map and shallow hydrogeological boreholes) has led us to propose a kinematic model of the Bizerte region since the Middle Miocene and to update the structural scheme. Then, the NE-SW major faults (e.g. the newly defined Sfaia-Metline fault) and the NW-SE secondary ones have controlled the paleogeography and the structuration of the study area. •The gravity inversion model highlight the lateral and vertical extension of anomalies.•New faults, non-observed at surface, are highlighted and characterized.•The location of some known major faults is confirmed.•Synthetic structural map based on sub-surface data has been established.•A kinematic model of the Bizerte area since the Middle Miocene is proposed.